1-2-3 draw knights, castles, and dragons a step by step guide - Levin, Freddie (Columbus, N.C. : Peel Productions, 2001)
Simple instructions for drawing dragons, knights and their weapons, and castles and the people who lived in them.
Basic shapes -- Basic person, front view -- King -- Basic person, side view -- Princess -- Basic person, running -- Prince -- Basic person, sitting -- Queen -- Castles -- Heraldry -- Knights -- Dragons -- Weapons -- Falconry -- Squires, pages, jesters and minerals.
Includes index.
5 - 10 years
Keywords: Knights and knighthood in art; Dragons in art; Castles in art; Drawing -- Technique; Knights and knighthood in art